Thermal patterning of superconducting films - Bekeris, V., author; Marconi, Mario Carlo, author; Tortarolo, M., author; Ferrari, H., author; Elsevier B. V., publisher (Colorado State University. Libraries, 2004)
The transient shape control of a superconducting high Tc film by selective optical heating has been addressed in this work, using a non-conventional technique that combines the application of a pulsed magnetic field and the optical heating of the superconducting film by a synchronized pulsed laser. A zero field cooled (ZFC) film was partially protected by a mask before exposing it to the laser radiation. The temperature at the illuminated area rises causing very fast local lowering of the vortex pinning force or may even rise above Tc. As a result, flux penetrates completely the heated area and an effective smaller sample remains in a superconducting critical state. Flux penetration is measured with a pick-up coil for different positions of the mask. Results are described within the critical state model for a strip, where the time integrated voltage signal is approximated to the flux difference between the initial ZFC sample and the final critical state of the "new" (cold) ZFC sample.
Keywords: dc magnetization; critical state; short time